Статут Глухівського педагогічного інституту 1920 р. - Мошик, І.В. (Сіверщина в історії України, 2021)
Стаття присвячена історії становлення радянської вищої освіти на початку 20-х років ХХ ст. На прикладі установчого документа Глухівського педагогічного інституту висвітлено організаційні процеси регіональної вищої школи в перехідний період від дореволюційних часів до початків формування освітніх доктрин нової більшовицької влади в Україні. Для об’єктивного сприйняття тогочасних реалій та їхніх впливів на соціально-політичне, духовне та етнокультурне формування нації, слід оприлюднювати і аналізувати документи, що формують джерельну базу, яка ілюструє здобутки та втрати української вищої школи на шляху її історичного становлення. Освітня система нашої держави на початку першого десятиліття панування радянської влади потерпала від реформаторських експериментів нових революційно налаштованих керівників, які діяли за принципом негайного руйнування здобутків минулого заради примарного щасливого майбутнього. Уся дореволюційна вища школа з її академічністю видалась українському більшовицькому уряду регресивно патріархальним пережитком минулого. Тому у цей період були проведені кардинальні зміни в системі української вузівської освіти. Глибоке наукове дослідження цих проблем є одним з гарантів незворотності позитивних змін у суспільстві. The article is devoted to the history of the formation of Soviet higher education in the early 20s of the twentieth century. The organizational processes of the regional higher school in the transition period from pre-revolutionary times to the beginning of the formation of educational doctrines of the new Bolshevik government in Ukraine are highlighted on the example of the constituent document of the Hlukhiv Pedagogical Institute. In order to objectively perceive the realities of that time and their influences on the socio-political, spiritual and ethnocultural formation of the nation, it is necessary to publish and analyze documents that form the source base, which illustrates the gains and losses of Ukrainian higher education. The educational system of our state at the beginning of the first decade of Soviet rule suff ered from the reform experiments of new revolutionary leaders, who acted on the principle of immediate destruction of the achievements of the past for the sake of a ghostly happy future. The entire pre-revolutionary higher school with its academicity seemed to the Ukrainian Bolshevik government a regressively patriarchal relic of the past. Therefore, during this period, radical changes were made in the system of Ukrainian higher education. An in-depth scientific study of these problems is one of the guarantees of the irreversibility of positive changes in society.